Rational Synthesis of 5, 5, 5‐Tricyclic Fused Thia‐heptaphyrin (1.1.1.1.1.1.0) From a Helical Oligopyrrin Hybrid. Issue 8 (13th March 2020) - Fu, Yating; Liu, Xiujun; Li, Chengjie; Tong, Zhangfa; Baryshnikov, Glib; Ågren, Hans; Li, Qizhao; Xie, Yongshu
Abstract: Oxidation of a thiophene‐hexapyrrane hybrid S‐P6 afforded a stable conjugated open‐chain thiaheptapyrrolic helix 1 with the terminal thiophene and confused pyrrole units lying at a long distance that is adverse for further cyclization. Chelation of 1 with copper(II) ion afforded 1‐Cu, which exhibits more distant terminal units. Interestingly, further oxidation of 1 triggered an intramolecular C−N fusion reaction to afford a unique 5, 5, 5‐tricyclic fused linear thiaheptapyrrin 2, with the two terminals positioned in proximity, which favors the oxidative ring‐closure reaction to give a unique 5, 5, 5‐tricyclic fused thiaheptaphyrin (1.1.1.1.1.1.0) 3 under air. The inner‐fusion strategy for positioning the reactive sites in proximity to promote oxidative cyclization offers a new approach for constructing large porphyrinoids through conjugated oligopyrrins without the assistance of metal ions. Abstract : Oxidation of a thiophene‐hexapyrrane hybrid S‐P6 afforded a conjugated thiaheptapyrrolic helix, which underwent an inner‐N‐fusion process to form a 5, 5, 5‐tricyclic fused thiaheptapyrrin, and further converted into thiaheptaphyrin (1.1.1.1.1.1.0) under air. The results provide an effective approach for constructing novel porphyrinoids from conjugated oligopyrrins.